Fourth Five-Year Plan Andhra Pradesh A Draft Outline - Planning Commission (Planning Commission, 1968)
The Planning Commission had suggested in February, 1968 that the States may undertake a review of economic development and the success of various programmes from 1950-51 onwards so that such an assessment would provide a basis for determining the objectives and priorities for the Fourth Five-Year Plan. The State Government had taken up such a review in September, 1967 itself and as a result a survey of the economic development of Andhra Pradesh from 1951 to 1968 was published in February, 1968.
Planning and Panchayati Raj Department, Government of Andhra Pradesh